Efektivitas Pembelajaran E-learning Dalam Meningkatkan Hasil Belajar Siswa di Sekolah Madrasah Ibtidaiyah Al-Hikmah Tajur - Nana Nuraeni; Dahlan Dahlan; Zahid Mubarok (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Education is something that is very important for every human being. Because education can build the quality of a nation, along with the development of increasingly advanced times, science and learning media are also growing The use of learning media such as e-learning, one of which is through web-based learning. In the research conducted by the author, the goal is to find out the effectiveness of e-learning on learning in madrasah Ibtidaiyah Al Hikmah Tajur. The research method used by the author is to use quantitative methods From the results of the author's research that has been described above that the Learning Effectiveness variable (X) is stated that there is no significant influence on the Learning Outcomes (Y) variable which the author has proven with the results that have been described using product moment correlation test. Keywords: Education, e-learning, effectiveness